2014
DOI: 10.1111/ajt.12908
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Tissue-Restricted Self-Antigens Induces Airway Inflammation and Fibrosis Following Murine Lung Transplantation

Abstract: Immune responses against lung-associated self-antigens (self-Ags) are hypothesized to play a role in the development of chronic lung graft rejection. We determined whether immune responses to lung self-Ags, K-alpha-1-tubulin (Kα1T) and Collagen V (Col-V) in the absence of alloimmunity, could promote airway inflammation and fibrosis. Following syngeneic murine orthotopic lung transplantation (LTx) we administered antibodies (Abs) to either Kα1T or Col-V or in combination to both of these self-Ags. As compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 26 publications
2
55
0
Order By: Relevance
“…These findings demonstrate that the effects of the lung-restricted antibodies are not global, but, rather, specific to the transplanted lung alone. We recently demonstrated that de novo lung-restricted antibodies, administered after lung transplantation, can mediate rejection of syngeneic lung grafts and predispose to chronic rejection (17). In the present article, we establish that preexisting lungrestricted antibodies lead to PGD in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…These findings demonstrate that the effects of the lung-restricted antibodies are not global, but, rather, specific to the transplanted lung alone. We recently demonstrated that de novo lung-restricted antibodies, administered after lung transplantation, can mediate rejection of syngeneic lung grafts and predispose to chronic rejection (17). In the present article, we establish that preexisting lungrestricted antibodies lead to PGD in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 60%
“…Th17 cells specific to sAgs play an important role in development of sAg-specific immune responses. Although we specifically did not block Th17, previous studies from our laboratory, and others, have shown that blocking of Th17 can prevent OAD (17,48). The phenomenon of tissue-restricted immunity leading to organ rejection has also been demonstrated in heart allograft, where antibodies against cardiac myosin have been shown to be pathogenic in chronic heart allograft rejection (49).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Given the advantage of genetics knockouts in mice and possibility of invasive sampling, this model is an excellent set-up to study underlying mechanisms. For example, it was shown that progressive loss of self-tolerance through epitope spreading promotes airway fibrosis (22). In another experiment, it has been shown that the murine lung allograft fibrosis originates mostly from the donor (23).…”
Section: Risk Factors and Mechanisms Of Bosmentioning
confidence: 99%